Convective activity in an extratropical cyclone and its warm conveyor belt – a case‐study combining observations and a convection‐permitting model simulation. (17th April 2019) - Oertel, Annika; Boettcher, Maxi; Joos, Hanna; Sprenger, Michael; Konow, Heike; Hagen, Martin; Wernli, Heini
Abstract : Warm conveyor belts (WCBs) are important Lagrangian features in extratropical cyclones for the evolution of clouds, precipitation and flow dynamics. According to the classical concept, WCBs rise continuously from the boundary layer to the upper troposphere with ascent rates of less than 50 hPa/hr. Recent studies identified embedded convection in WCBs with ascent rates exceeding 50 hPa/hr, however, its significance and characteristics have not yet been analysed systematically. This study presents a detailed analysis of a frontal wave cyclone that occurred during the North Atlantic Waveguide and Downstream Impact Experiment (NAWDEX) and investigates the occurrence of convection with ascent rates exceeding 100–200 hPa/hr embedded in the WCB. A set of diagnostics, based on the combination of Meteosat products, ECMWF data, and a convection‐permitting simulation, reveals consistently that convection occurs frequently in the warm sector of the investigated cyclone, in particular in the region of the WCB. These convective regions are characterized by increased surface precipitation, low values of convective available potential energy, and significant large‐scale forcing for ascent, indicating that this type of convection embedded in WCBs differs from classical air mass convection with higher vertical velocities. This is qualitatively confirmed by airborne radar observations of the considered cyclone with reflectivities hardly exceeding 30 dBZ. In the investigated WCB, the ascent is not continuous, but characterized by intermittent periods of very strong or even convective ascent and occasionally by short periods of descent. Together, these results provide a refined view on the concept of WCBs and its embedded convection. Abstract : Convection is a ubiquitous element of extratropical cyclones, frequently embedded in its warm conveyor belt. Despite the potential importance of embedded convection in the warm conveyor belt for the large‐scale dynamics and surface precipitation, its role has not yet been investigated in detail. In this study, we combine complementary observations with online trajectories from convection‐permitting simulations to identify and characterize embedded convection and provide a refined view of the "escalator–elevator" concept of the warm conveyor belt.